AB0615 Persistence of human papillomavirus in the cervix of women with systemic sclerosis. (15th June 2017) - Vacchi, C; Colaci, M; Cassone, G; Esposito, C; Lumetti, F; Giuggioli, D; Ferri, C
Abstract : Background: Persistent infection by high-risk oncogenic Human Papillomavirus (HPV) is the main cause of the development of dysplastic or malignant lesions of the cervix. Furthermore, a few life habits, such as smoking, sexual habits and hormonal contraception, are known risk factors for cervical HPV infection. In addition, increased frequency of persistent HPV infection or high-grade intra-epithelial lesions rates was anecdotally described in patients affected by immune-mediated diseases, such as systemic lupus erythematosus, rheumatoid arthritis and systemic sclerosis (SSc), in comparison with the general population. Objectives: To determine the prevalence of persistent HPV infection in an SSc patients series and its possible correlation with the disease clinical features. Methods: The study retrospectively evaluated 52 consecutive female SSc patients (age 56.7±11.2SD years, disease duration 12.1±7.4SD years), classified according to the ACR/EULAR 2013 criteria, referring to our university-based Rheumatology Unit. Detection of HPV DNA and viral genotyping in cervical swabs were carried out. Moreover, abnormal Papanicolau test smears were classified using the Bethesda system. Results: Fourteen(26.9%) patients presented a cervical swab positive for HPV infection, including12 infected by high risk or probable-high risk HPV types. Six (11.5%) patients presented multiple infection (≥2 HPV types), including one case with high-grade intra-epithelial lesion. Only tabagism was significantly correlated to HPV infection; namely, smoking habit was observed in 41.6% of SSc patients with and in 21.7% of those without HPV infection, respectively; p=0.006); moreoverimmunesuppressive therapies, namely mofetil mycophenolate, cyclophosphamide or rituximab, tended to be associated withHPV infection (presence/absence 21.4 vs 21.7%; p=0.055). More interestingly, amongSSc patients over 50, HPV infection was found in 9/38 (23.7%) individuals, a frequency markedly higher than that expected in age-matched general population from the same geographical area (5%). Conclusions: Persistent HPV infection was observed in over a quarter of SSc patients, notably in women over 50. The HPV positivity was not related to SSc clinical features, while a significant association with tabagism and immunesuppressive therapies was evidenced. Considering the possible clinico-prognostic implication on the overall disease outcome, routinely gynaecological screening of SSc female patients ishighly recommendable. Disclosure of Interest: None declared